Arti Petuah Matiti Suara dalam Upacara Ngusaba Kedasa di Pura Ulun Danu Batur, Kintamani, Bangli - Jutama, I Nengah Eris (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Matiti Suara is one of the traditions to complete Yadnya carried out in Ulun Danu Batur Temple. Matiti Suara Derived from two words, namely Titi which means Jalan Utawi Bridge, Suara means Sound and gets the prefix -ma, so Matiti Suara is a sound or sound that becomes a road or bridge so that you do good in life. Ulun Danu Batur. The formulations of the research problem are: (1) What is the Order of Matiti Suara at Ngusaba Kedasa at Ulun Danu Batur Temple, (2) What are the benefits of Matiti Suara for the people in Batur Village? (3) What is the Meaning of Matiti Suara that is carried out at Ulun Danu Batur Temple. The theory used to research this research is Structural Functional Theory and Value Theory. The data sources obtained are based on observation methods, interviews, literature and documentation. After the data is obtained, then the data is analyzed or processed based on data reduction techniques, data display, and data verification. The data obtained based on this research is the meaning of the first Matiti Suara's Piteket, namely Baas Barak Baas Putih, Ané Daak Dados Sugih, the second, namely Mula Kliki, Mula Biu, Mula Kidik Mupu Liu, the third, namely Sampunang Nganggé Kriya Usaha Dhana Prestasiné, and the third four, namely giving or giving Uang Képeng.